2019
DOI: 10.1016/j.eurpsy.2018.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Maternal violence experiences and risk of postpartum depression: A meta-analysis of cohort studies

Abstract: Background:Most of original studies indicated maternal violence experiences is associated with adverse obstetric outcomes, to date, but it is not clear that the association of maternal violence experiences and the risk of postpartum depression (PPD). We aimed to assess the association between maternal violence experiences and risk of developing PPD by performing a meta-analysis of cohort studies.Methods:PubMed, Google Scholar, Cochrane Libraries and Chinese databases were searched through December 2017 to iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 56 publications
(80 reference statements)
2
25
1
3
Order By: Relevance
“…The literature on risk factors for PPD, including low social support [25], low social economic status [26], cigarette smoking [27], low sleep quality [28,29], unplanned pregnancy [26], and intimate partner violence [30] is substantial. The potential risk factors for PP-PTSD include childhood sexual abuse [31], intimate partner violence [31], low social support [32], instrumental birth, and caesarean section [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…The literature on risk factors for PPD, including low social support [25], low social economic status [26], cigarette smoking [27], low sleep quality [28,29], unplanned pregnancy [26], and intimate partner violence [30] is substantial. The potential risk factors for PP-PTSD include childhood sexual abuse [31], intimate partner violence [31], low social support [32], instrumental birth, and caesarean section [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, diverse kinds of violence such as sexual, emotional, and physical violence, as well as other forms of domestic or childhood violence also increased the risk of developing PPD. 19 Less well understood, however, is the relationship between postpartum depression and earlier experiences such as childhood maltreatment or abuse. 20,21 The WHO multi-country study found prevalence of physical partner violence in pregnancy ranging from 1% in urban Japan to 28% in provincial Peru, with prevalence in most sites of 4-12%.…”
Section: Introductionmentioning
confidence: 99%
“…According to the data of our study, 27.1% of the patients presented with mild or more severe depression, which is three times higher than in the USA (19). A highly probable explanation of this difference is the summary of unfavourable conditions for a happy and satisfactory pregnancy, and more violence of any kind against pregnant women that increases the risk of depression (20,21). Also, it can be inferred that phenomena such as machismo, sexism, and even feminicide con-tribute to a very dangerous situation for pregnant women in some Mexican municipalities.…”
Section: Discussionmentioning
confidence: 49%